Analysis of factors affecting economic growth in industrial enterprises of Kashakadarya region - Mirzayev Abdalimovich, Zafar (THE INNOVATION ECONOMY, 2024)
This article analyzes the essence of economic growth of industrial enterprises in the region and its role in the economy, as well as factors influencing the economic development of industrial enterprises. Also, the effective development of an industrial enterprise is based on the diversification of its modern industries and increasing the volume of output of modern industrial products, creating certain socio-economic conditions to increase the labor potential in society, ensuring employment of the population, increasing the volume of gross domestic product, dividing the population into industrial products, issues are highlighted creating demand for labor, expanding the division of labor. Before the stage of development of industrial enterprises in the regions, priority in ensuring economic growth was given to natural and labor resources, and at the stage of development of industrial enterprises - to material resources; at the present stage, after the development of industrial enterprises, the role of intellectual and information resources comes to the fore. The development of the leading countries of the world has led to the formation of a new economy of knowledge, innovation, global information systems, new technologies, and venture business. The analysis of these data is reflected in this article.